Insights into the remediation characterization of modified bentonite in minimizing organosulphur compounds from diesel fuel - Khalili, Fawwaz I.; Sultan, Mohammed; Robl, Christian; Al-Ghouti, Mohammad A. (Journal of industrial and engineering chemistry (Seoul, Korea), 2015)
•ORS uptake was marginally affected with the particle size.•ORS mainly uptakes on the external surface area of the adsorbents.•Acid activation process enhanced the adsorptive efficiency of AB.•Acid activation process did increase the AB's surface area and pore volumes.•ORS that was adsorbed by AB (4.7920mg S/g) is more than that adsorbed by TB. In this work, physical and chemical characteristics of the raw, treated, and acid activated bentonite were investigated using XRD, FTIR, scanning electron microscopy (SEM), and differential thermal analysis (DTA)/thermogravimetry (TG) analysis and surface area and porosity determination techniques. The organosulphur compounds (ORS) uptake was slightly affected by the particle size indicating that the removal of ORS mainly occurred on the external surface of the modified bentonite samples. The acid activation process enhanced the adsorptive efficiency of the bentonite sample through increasing both the surface area and the pore volume, in addition to the release of a considerable amount of interlayer cations of the clay.